2011
DOI: 10.1136/bcr.04.2011.4135
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of tocilizumab in polymyalgic onset biopsy positive GCA with large vessel involvement

Abstract: A 63-year-old female presented with a 12-week history of worsening proximal pain and stiffness. She was diagnosed with polymyalgia rheumatica and started on corticosteroids. The authors were unable to wean-off her steroid treatment, despite trying various steroid sparing agents on different occasions with no benefit. In August 2010, she was diagnosed with giant cell arteritis with a temporal artery biopsy and ultrasound of the temporal and axillary arteries. An fluorine-18-deoxyglucose positron emission tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 22 publications
0
13
0
3
Order By: Relevance
“…Some published reports showed the ability of TCZ to induce remission or to reduce glucocorticoids [7][8][9][10][11][12][13][14][15][16][17]55]. The tapering of corticoids to less than 7.5 mg/day was obtained after 3 to 8 months of treatment by TCZ in some reports [7,9,10,13,55]. Seitz et al [55] reported that prednisone dosage could be reduced within 3 months to a mean of 2.5 mg/day (range 0-10 mg/day) in 5 patients with GCA( two of them were newly diagnosed and not treated by corticoids before).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some published reports showed the ability of TCZ to induce remission or to reduce glucocorticoids [7][8][9][10][11][12][13][14][15][16][17]55]. The tapering of corticoids to less than 7.5 mg/day was obtained after 3 to 8 months of treatment by TCZ in some reports [7,9,10,13,55]. Seitz et al [55] reported that prednisone dosage could be reduced within 3 months to a mean of 2.5 mg/day (range 0-10 mg/day) in 5 patients with GCA( two of them were newly diagnosed and not treated by corticoids before).…”
Section: Discussionmentioning
confidence: 99%
“…Tocilizumab (TCZ), an interleukin 6 receptor antibody, was considered, on the basis of pathogenic and pathologic data of GCA, as a potentially effective treatment for this disease .The drug showed efficacy in few case reports and small series [7][8][9][10][11][12][13][14][15][16][17]. Here we report 2 cases with Giant cell arteritis that was dependent to corticoids, successfully treated by TCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, serum IL-6 levels mirror the activity of the disease, and decline with effective GC therapy, suggesting a potential therapeutic role for the IL-6 receptors inhibitor monoclonal antibody tocilizumab (TCZ) [16]. Case reports and small case series have shown the efficacy of TCZ in the treatment of patients with relapsing/refractory GCA [17][18][19][20][21][22][23][24]. A smaller number of newly diagnosed GCA patients naive to GC and other immunosuppressive agents has also successfully been treated with TCZ monotherapy [18,25].…”
Section: Giant Cell Arteritismentioning
confidence: 97%
“…Recently, treatment with the interleukin-6 inhibitor, tocilizumab, has been shown to be effective in patients with giant cell arteritis. [75][76][77] Tocilizumab is indicated in a subgroup of patients with giant cell arteritis and profound constitutional symptoms, a high systemic inflammatory response, and active disease, with involvement of the aorta and its main branches. Larger studies with this therapeutic agent are awaited.…”
Section: Biologic Agentsmentioning
confidence: 99%